Copper-Induced Activation of MAPKs, CDPKs and CaMKs Triggers Activation of Hexokinase and Inhibition of Pyruvate Kinase Leading to Increased Synthesis of ASC, GSH and NADPH in Ulva compressa - Laporte, Daniel; González, Alberto; Moenne, Alejandra (Frontiers in Plant Science, 2020)
In order to analyze whether copper induces activation of CaMK, CDPK and/or MAPK signaling pathways lead to carbon flux reprogramming and to the synthesis of ascorbate (ASC), glutathione (GSH) and NADPH to cope with oxidative stress, U. compressa was initially cultivated with 10 μM copper for 0 to10 days. The activities of hexokinase (HXK), pyruvate kinase (PK), L-galactone 1,4 lactone dehydrogenase (L-GLDH) and glucose 6-P dehydrogenase (G6PDH) were analyzed. HXK activity was increased whereas PK was inhibited, and L-GLDH and G6PDH activities were increased indicating a copper-induced modulation of glycolysis that lead to carbon flux reprogramming. Then, the alga was cultivated with an inhibitors of CaMs and CaMK, CDPKs and MAPKs, and with 10 μM of copper for 5 days and the activities of HXK, PK, L-GLDH, G6PDH and glutathione synthase (GS), the levels of ASC/DHA, GSG/GSSG and NADPH/NADP and the levels of superoxide anions (SA) and hydrogen peroxide (HP) were determined. The activation of HXK was dependent on MAPKs, the inhibition PK on CDPKs/MAPKs, the activation of L-GLDH on MAPKs, and the activation GS on CDPKs and MAPKs, and the activation of G6PDH on MAPKs. Increases in the level of ASC/DHA were dependent on activation of CaMKs/CDPKs/MAPKs, those of GSG/GSSG on MAPKs and those NADPH/NADP on CaMKs/CDPKs/MAPK. The accumulation of superoxide anions and hydrogen peroxide was dependent on CaMK, CDPKs and MAPKs. Thus, copper induced the activation of MAPKs, CDPKs and CaMK leading to the modulation of glycolysis and induction of carbon flux reprogramming which trigger an increase in ASC, GSH and NADPH syntheses that mitigate copper-induced oxidative stress.